PENGARUH JUMLAH LILITAN DAN JENIS MATERIAL COIL PADA PV SOLAR ELECTRIC WARMER DOC - Muhamad Zulvi Anam; Asrori Asrori (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2023)
DOC brooding period where chicks need heating for development for 14 days with temperatures of 30°C-34°C. During the use of ordinary heating devices, another alternative is to use solar panel-based electric heating because it can save energy sources. The objectives of this research are (1) to determine the effect of variations in the number of coil material turns from 20, 30 and 40 turns on the heat produced by the PV Solar Electric Warmer DOC, (2) to determine the effect of the thermal conductivity of the coil material (copper and nickel) on the heat generated. produced by PV Solar Electric Warmer DOC. The method used is experimental by varying the number of coil windings using thermal conductivity of copper and nickel materials to the heat generated by PV Solar Electric Warmer DOC. The use of variations in the number of coil windings in this study was 20, 30 and 40. The results of this study are the greater the number of coil windings and the type of thermal conductivity affects the heat generated by PV Solar Electric Warmer DOC. In the test copper coil with winding 20 has an average temperature of 30°C, winding 30 averaging 31°C and winding 40 averaging 31°C. When testing nickel materials with the number of windings 20 have an average of 31°C, winding 30 averaging 32°C and winding 40 averaging 33°C. In thermal conductivity testing, nickel coil material reaches the highest temperature of 35° C and copper coil testing reached a high temperature of 32°C